Sense of coherence in adults with congenital heart disease in 15 countries: Patient characteristics, cultural dimensions and quality of life. (11th June 2020) - Moons, Philip; Apers, Silke; Kovacs, Adrienne H; Thomet, Corina; Budts, Werner; Enomoto, Junko; Sluman, Maayke A; Wang, Jou-Kou; Jackson, Jamie L; Khairy, Paul; Cook, Stephen C; Chidambarathanu, Shanthi; et al.
Abstract: Background: Previous studies have found that sense of coherence (SOC) is positively related to quality of life (QoL) in persons with chronic conditions. In congenital heart disease (CHD), the evidence is scant. Aims: We investigated (i) intercountry variation in SOC in a large international sample of adults with CHD; (ii) the relationship between demographic and clinical characteristics and SOC; (iii) the relationship between cultural dimensions of countries and SOC; and (iv) variation in relative importance of SOC in explaining QoL across the countries. Methods: APPROACH-IS was a cross-sectional, observational study, with 4028 patients from 15 countries enrolled. SOC was measured using the 13-item SOC scale (range 13–91) and QoL was assessed by a linear analog scale (range 0–100). Results: The mean SOC score was 65.5±13.2. Large intercountry variation was observed with the strongest SOC in Switzerland (68.8±11.1) and the lowest SOC in Japan (59.9±14.5). A lower SOC was associated with a younger age; lower educational level; with job seeking, being unemployed or disabled; unmarried, divorced or widowed; from a worse functional class; and simple CHD. Power distance index and individualism vs collectivism were cultural dimensions significantly related to SOC. SOC was positively associated with QoL in all participating countries and in the total sample, with an explained variance ranging from 5.8% in Argentina to 30.4% in Japan. Conclusion: In adults with CHD, SOC is positively associated with QoL. The implementation of SOC-enhancing interventions might improve QoL, but strategies would likely differ across countries given the substantial variation in explained variance.